Analysis of the quality of life of institutionalized elderly: systematic literature review (Research, Society and Development, 2021)
Introduction: Aging is still configured as an irreversible, inevitable and inherent process to the entire population. Objective: to gather existing evidence in the literature on the performance of exercises to improve the functionality of institutionalized elderly people. Methodology: Data analysis was carried out from November 2020 to March 2021. The research was carried out by searching the databases of PEDro (Database on Evidence in Physiotherapy (Portuguese/English), PubMed (US National Library of Medicine National Institutes of Health ), and Cochrane (Library). With clinical trials published in English and Portuguese, from 2016 to 2020. Articles published in the last 5 years in Portuguese and English, carried out on human beings, were included. , with the text available in full and free of charge, with the elderly and who were institutionalized. Studies that did not meet the inclusion criteria were excluded, as well as monographs, review articles, master's and doctoral theses and letters to the editor. Results: 13,435 files were found, of which only 5 clinical trials were suitable for the study according to the inclusion criteria. Discussion: The results demonstrate that strategies such as physical activity, exercises associated with verbal stimulation, functional training and the practice of activities of daily living, proved to be valid alternatives to provide independence and autonomy in performing the AVDS. Final Considerations: The study showed that the use of evidence-based multicomponent interventions provide benefits to the functionality, quality of life, cognitive and emotional state of institutionalized elderly.